Intimate Activism : the Struggle for Sexual Rights in Postrevolutionary Nicaragua. - Howe, Cymene (Duke University Press Books, 2013)
Intimate Activism tells the story of Nicaraguan sexual-rights activists who helped to overturn the most repressive antisodomy law in the Americas. The law was passed shortly after the Sandinistas lost power in 1990 and, to the surprise of many, was repealed in 2007. In this vivid ethnography, Cymene Howe analyzes how local activists balanced global discourses regarding human rights and identity politics with the contingencies of daily life in Nicaragua. Though they were initially spurred by the antisodomy measure, activists sought to change not only the law but also culture. Howe e.